2016
DOI: 10.1016/j.nicl.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Giant early components of somatosensory evoked potentials to tibial nerve stimulation in cortical myoclonus

Abstract: Enlarged cortical components of somatosensory evoked potentials (giant SEPs) recorded by electroencephalography (EEG) and abnormal somatosensory evoked magnetic fields (SEFs) recorded by magnetoencephalography (MEG) are observed in the majority of patients with cortical myoclonus (CM). Studies on simultaneous recordings of SEPs and SEFs showed that generator mechanism of giant SEPs involves both primary sensory and motor cortices. However the generator sources of giant SEPs have not been fully understood as on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Another limitation in deriving neurophysiological features from SEP signal amplitudes involves the fact that in group comparisons, differences in underlying tissue properties between groups potentially affect SEP amplitude. In longitudinal studies, this issue is addressed by normalizing SEP amplitudes to baseline values and then comparing changes in relative SEP amplitude between different groups (McGregor et al, 2015 ; Andrade et al, 2016 ; Anzellotti et al, 2016 ). However, in cross-sectional studies, this possibility does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation in deriving neurophysiological features from SEP signal amplitudes involves the fact that in group comparisons, differences in underlying tissue properties between groups potentially affect SEP amplitude. In longitudinal studies, this issue is addressed by normalizing SEP amplitudes to baseline values and then comparing changes in relative SEP amplitude between different groups (McGregor et al, 2015 ; Andrade et al, 2016 ; Anzellotti et al, 2016 ). However, in cross-sectional studies, this possibility does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Eberhardt and Topka [17], found giant median nerve SSEP responses (P27/N35) following N20 response of normal size may be observed in some types of myoclonus. The majority of studies showed evidence of giant SSEPs only to median nerve stimulation; these giant SSEPs consisted of the increased amplitude of the components appearing after the N20, by the appearance of high amplitude complexes in the latency range of P25-N30 and P25-N30 complex [25]. These "giant" potentials can be seen in myoclonus of different origins such as PME, PHM (Lance-Adams syndrome), Alzheimer's disease, Creutzfeldt-Jakob disease, and metabolic encephalopathy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Typický je nález tzv. "giant SEP" u myoklonické epilepsie, kdy hodnoty amplitud korových odpovědí SEP mohou být více než 10 uV (Anzellotti et al, 2016).…”
Section: Zvýšení Amplitudyunclassified